Dinamika Kebijakan Ganja Dalam Politik Hukum Global dan Indonesia - Pangaribuan, Aristo (Jurnal Hukum & Pembangunan, 2024)
This article discusses legal and political issues related to marijuana in global literature and its influence in the Indonesian context. Moreover, this article also tries to predict the dynamics of the ongoing reform process related to Indonesian narcotic laws. To achieve such missions, mainly, this article summarizes the debate within marijuana literature and highlights its influence within the Indonesian context. The first part of this article discusses the legal and political dynamics of marijuana laws globally. Here, this article found that there is a paradigm shift toward marijuana use -- from a crime problem to a health problem. Subsequently, this article also analyzes whether such a paradigm shift might happen in Indonesia. In the end, this article found that such a paradigm shift will not likely occur in Indonesia because of several reasons. First, there is a tendency for Indonesian lawmakers to treat marijuana issues with the communitarianism principle. As a result, it makes the government act as a "moral guardian" for its citizens. This is because the use of marijuana is not only treated as a legal issue but also a moral one. The process of internalization of previous laws creates a negative moral stigma. As a consequence, a paradigm shift in the reform will face tough challenges. The recent criminal code (KUHAP nasional) also introduces the punitive drug law's logic. Lastly, the flexibility in interpreting the current regulations (2009) will create resistance to reform from the legal apparatus. Most likely, legal apparatus will not surrender their "comfort zone" due to the current law's flexibility that prioritizes punitive actions.